Proceedings of the 2006 International Symposium on Physical Design 2006
DOI: 10.1145/1123008.1123050
|View full text |Cite
|
Sign up to set email alerts
|

Improved method of cell placement with symmetry constraints for analog IC layout design

Abstract: Recently, it is often required in high performance analog IC design that some cells are placed symmetrically to horizontal or vertical axis. Balasa et al. proposed a method of obtaining the closest placement satisfying the given symmetry constraints and the topology constraints imposed by a sequence-pair, but this method has the following defects: (1) Some cells overlap each other. (2) The closest cell placement satisfying both the symmetry and topology constraints may not be obtained. (3) How to place cells s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 10 publications
(44 reference statements)
1
29
0
Order By: Relevance
“…It has been shown in [1] that a sufficient symmetry feasible condition [8] in a SP (s 1 , s 2 ) is the following.…”
Section: A Initial Scanmentioning
confidence: 99%
“…It has been shown in [1] that a sufficient symmetry feasible condition [8] in a SP (s 1 , s 2 ) is the following.…”
Section: A Initial Scanmentioning
confidence: 99%
“…It is pointed out in [6] that condition (1) is sufficient but not necessary. More recently, the work of [3] presented another sequence-pair based approach for simultaneously satisfying symmetry and centroid constraints.…”
Section: Previous Work With Symmetry Constraintsmentioning
confidence: 99%
“…Lin et al [11] also presented the symmetric-feasible conditions for the TCG-S representation. Two more recent works [9,14] further took advantage of the symmetryfeasible condition in sequence pairs [1]. Kouda et al [9] proposed a linear programming based method, and Tam et al [14] introduced a dummy node and additional constraint edges for each symmetry group after obtaining a symmetric-feasible sequence pair.…”
Section: Previous Workmentioning
confidence: 99%
“…Two more recent works [9,14] further took advantage of the symmetryfeasible condition in sequence pairs [1]. Kouda et al [9] proposed a linear programming based method, and Tam et al [14] introduced a dummy node and additional constraint edges for each symmetry group after obtaining a symmetric-feasible sequence pair. Most of the previous works showed that the symmetricfeasible conditions in the topological representations can handle the placement problem with a symmetry group effectively.…”
Section: Previous Workmentioning
confidence: 99%